New injectable elastomeric biomaterials for hernia repair and their biocompatibility. (January 2016) - Skrobot, J.; Zair, L.; Ostrowski, M.; El Fray, M.
Abstract: Complications associated with implantation of polymeric hernia meshes remain a difficult surgical challenge. We report here on our work, developing for the first time, an injectable viscous material that can be converted to a solid and elastic implant in vivo, thus successfully closing herniated tissue. In this study, long-chain fatty acids were used for the preparation of telechelic macromonomers end-capped with methacrylic functionalities to provide UV curable systems possessing high biocompatibility, good mechanical strength and flexibility. Two different systems, comprising urethane and ester bonds, were synthesized from non-toxic raw materials and then subjected to UV curing after injection of viscous material into the cavity at the abdominal wall during hernioplasty in a rabbit hernia model. No additional fixation or sutures were required. The control group of animals was treated with commercially available polypropylene hernia mesh. The observation period lasted for 28 days. We show here that artificially fabricated defect was healed and no reherniation was observed in the case of the fatty acid derived materials. Importantly, the number of inflammatory cells found in the surrounding tissue was comparable to these found around the standard polypropylene mesh. No inflammatory cells were detected in connective tissues and no sign of necrosis has been observed. Collectively, our results demonstrated that new injectable and photocurable systems can be used for minimally invasive surgical protocols in repair of small hernia defects.